Response of GOLD Retrieved Thermospheric Temperatures to Geomagnetic Activities of Varying Magnitudes. Issue 15 (2nd August 2021) - Laskar, F. I.; Eastes, R. W.; Codrescu, M. V.; Evans, J. S.; Burns, A. G.; Wang, W.; McClintock, W. E.; Aryal, S.; Cai, X.
Abstract: Global‐scale Observations of Limb and Disk (GOLD) disk measurements of far ultraviolet molecular nitrogen band emissions are used to retrieve temperatures ( T d i s k ), which are representative of lower thermospheric altitudes. The present investigation studies the response of lower thermospheric temperatures to geomagnetic activities of varying magnitudes. In this study, it has been observed that T d i s k increases over all latitudes in response to enhanced geomagnetic activity. The increase in temperature is proportional to the strength of the geomagnetic activity and is greater at higher latitudes. Temperature enhancements vary from 10s to 100s of Kelvins from low‐ to mid‐latitudes. Local time behavior shows that pre‐noon enhancements in temperatures, during relatively stronger geomagnetic activities, are greater compared to afternoon, which may be caused by the combined action of daytime dynamics and geomagnetic forcing. This study, thus, demonstrates the utility of GOLD T d i s k when investigating the effects of dynamical and external forcings in the thermosphere. Plain Language Summary: The thermosphere ionosphere system is influenced by waves from the lower atmosphere and solar and geomagnetic forcing from above. For such a coupled system it is important to decipher the relative influence of the two regimes of forcings. The recently launched Global‐scale Observations of Limb and Disk (GOLD) mission provides daytime thermospheric temperatures with unprecedented local time and spatial coverage. The thermospheric temperature over the Earth's disk visible from geostationary orbit is a first of its kind of measurement, which enables us to investigate the local time behavior over wide latitudinal coverage from 69 ° S to 69 ° N. We find that, during active geomagnetic conditions, the thermospheric temperature is enhanced across the whole visible hemisphere, with the largest temperature enhancements at higher mid‐latitudes. The local time behavior shows that the pre‐noon enhancement in temperature is greater compared to the afternoon, which demonstrates, for the first time, a systematic local time varying response of thermosphere to geomagnetic forcing. Key Points: Global‐scale Observations of Limb and Disk (GOLD) thermospheric temperature increases globally in response to geomagnetic activity The increase in temperature is proportional to the strength of the activity and is greater at higher latitudes Temperature enhancement during active geomagnetic events is greater in the morning than that in the afternoon